Composition of species, utilization, and conservation status of plant species in the sugar palm (Arenga pinnata) agroforestry system - Kadir, ​Zen Setiawan; Baderan, Dewi Wahyuni K.; Marini S. Hamidun (Institute for Advanced Science, Social, and Sustainable Future (IASSSF), 2025)
Background: The goal of agroforestry is to integrate perennial crops, seasonal crops, and livestock to increase income, protect the environment, and support sustainable resource management by maintaining soil fertility, biodiversity, and food security. The agroforestry system's principal components, such as trees, agricultural crops, and livestock, are interdependent to optimize and sustainably utilize resources. This study aims to determine the composition of plant species in sugar palm (Arenga pinnata) agroforestry, to identify plant utilization, and to assess the conservation status of plant species within the sugar palm agroforestry system. Methods: This study employed a quantitative approach, using survey methods and plant data collection by exploring the research site and observing all plant species present, accompanied by photography using a digital camera. Findings: The results indicate that the sugar palm (Arenga pinnata) agroforestry system has significant potential in supporting environmental sustainability and community welfare. A total of 31 plant species were identified, with 12 of them having recorded data in the IUCN with a Least Concern category. Conclusion: Based on data from the IUCN Red List, 10 identified species are distributed in Sulaw esi Island, including Pangium edule Reinw, Arenga pinnata (Wurmb) Merr., Musa acuminata Colla, Hellenia speciosa (J.Koenig) S.R.Dutta, Macaranga tanarius (L.) Müll.Arg., Mimosa pudica L., Ficus septica Burm.f., Tacca leontopetaloides (L.) Kuntze, Ceiba pentandra (L.) Gaertn., and Ficus minahassae (de Vriese & Teijsm.) Miq. Novelty/Originality of this article: The novelty of this research lies in its comprehensive exploration of plant species composition, utilization, and conservation status within the sugar palm (Arenga pinnata) agroforestry system.